Effects of Spatial Experiences & Cognitive Styles in the Solution Process of Space-Based Design Problems in the First Year of Architectural Design Education - Erkan Yazıcı, Yasemin (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2013)
There are many factors that influence designers in the architectural design process. Cognitive style, which varies according to the cognitive structure of persons, and spatial experience, which is created with spatial data acquired during life are two of these factors. Designers usually refer to their spatial experiences in order to find solutions to design problems. Information recalled from past spatial experiences lay the ground for creating the conceptual framework when solving a design problem. In addition, the person's cognitive style, which develops through factors such as education, environment, genetics and family, can also be effective in solving design problems. In this line, an empirical study was conducted to research the effects of spatial experiences and cognitive styles on the solution process of spatial design problems in the first year of architectural design education. The study concluded that the cognitive styles of students were effective on their space creation method, order and duration.
Keywords: spatial experience; cognitive styles; design problems; design education; mekansal deneyim; bilişsel stiller; tasarım problemleri; tasarım eğitimi